Left atrial strain imaging differentiates cardiac amyloidosis and hypertensive heart disease - Rausch, Karen; Scalia, Gregory M.; Sato, Kei; Edwards, Natalie; Lam, Alfred King-yin; Platts, David G.; Chan, Jonathan (International journal of cardiac imaging, 2021)
Echocardiographic diagnosis of cardiac amyloidosis (CA) can be difficult to differentiate from increased left ventricular (LV) wall thickness from hypertensive heart disease. The aim of this study was to evaluate left atrial (LA) function and deformation using strain and strain rate (SR) imaging in cardiac amyloidosis. We reviewed 44 cases of CA confirmed by tissue biopsy or a combination of clinical and cardiac imaging data. Cases were classified according two subgroups: amyloid light chain (AL) or amyloid transthyretin (ATTR). These subjects underwent 2D-Speckle tracking echocardiographic derived (STE) LA strain analysis. These were compared to 25 hypertensive (HT) patients with increased LV wall thickness. The three phases of LA function were evaluated using strain and strain rate parameters. Despite a similar increase in LV wall thickness, all LA strain parameters were significantly reduced in the AL cohort compared to the HT cohort (reservoir strain/LAs: 11.0 vs. 24.8%, p < 0.05). The ATTR cohort had significantly thicker LV walls and higher atrial fibrillation burden compared to AL and HT patients but similar reduction in LA strain values compared to AL group. A reservoir strain (S-LAs) cut off value of 20% was 86.4% sensitive and 88.6% specific for detecting CA compared to HT heart disease in this cohort. LA strain parameters were able to identify LA dysfunction in all types of CA. LA function in CA is significantly worse compared with hypertensive patients despite similar increase in LV wall thickness. In combination with other clinical and imaging features, LA strain may provide incremental value in differentiating cardiac amyloidosis from increased wall thickness secondary to hypertension.